Corrosion permeability resistance of concrete with nanoplastics as admixture. Issue 1 (1st January 2021) - Yalley, Peter P. K.
Abstract: This study was conducted to ascertain the effect of nanoplastics on corrosion permeability resistance of concrete. Various percentages of nanoplastics ranging from 5% to 25% were used to replace cement in this study. The corrosion permeability resistance test and bond strength test were conducted in conformity with BS EN 12, 504–3:2005 and ASTC 1202, respectively. The results of this study depicted that specimen with 15% nanoplastics lost 40% of their bond strength from the zero corrosion stage to severe corrosion stage, while the specimens with no nanoplastics lost 90% of their bond strength. The addition of nanoplastics as an admixture to concrete provided an average range of 40% to 65% better corrosion protection than the plain concrete. The lower current reading of concrete specimens with nanoplastics compared to that of plain concrete signified the beneficial effect in using nanoplastics as an admixture in concrete to protect the reinforcing bars from corrosion. The study concludes that the initial lower current passing, lower current reading with prolonged time to reach the severe corrosion stage, smaller percentage loss of bond strength, mass and rib profile of concrete specimens with nanoplastics indicated higher resistivity of the concrete with nanoplastics. The study therefore recommends that nanoplastics should be used as an admixture to concrete up to 15% replacement level.